REVIEW APLIKASI SENSOR PADA SISTEM MONITORING DAN KONTROL BERBASIS MIKROKONTROLER ARDUINO - Anantajaya, I. M. R. A; Kumara, I. N. S.; Divayana, Y. (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p20, 2022)
Arduino microcontrollers have been widely used in research and society. The Arduino is equipped with one or more physical sensors to convert physical quantities into electrical signals that can be processed by the microcontroller. This paper reviews sensors, types of Arduino, and their application as a monitoring system. Data were obtained from platforms discussing online Arduino projects, scientific articles, electronic/micro-electronic component manufacturer sites, and other reliable sources. The results show that the sensors that are commonly used include temperature and humidity sensors DHT11, DHT22, Thermistor and LM35, limit switch touch sensors, proximity sensors HC-SR04, and Paralax PIR, gas sensors MQ2, MQ3, MQ5, MQ6, MQ7, MQ8, and MQ135 correspond to detected gases, ADXL345 and A3144 acceleration and magnet sensors, TCS3200 and TCS 34752 color sensors, KY-026 and Robotdyn IR fire sensors, KY-022 and KY-005 Infrared sensors, LDR and TSL2561 light sensors, voltage-current sensors ACS712 and PZEM-004T, and heart rate sensors KY-039 and MAX30102. While the microcontrollers that are often used include Arduino Uno, Arduino Nano, Arduino Mega, and other microcontrollers. Applications that have been developed include applications in the fields of health, agriculture and farm, creation of robots, security to vehicles.